Follicular Bronchiolitis: Two Cases with Varying Clinical and Radiological Presentation. (27th January 2020) - Garg, Delyse; Mody, Mohit; Pal, Chaitanya; Patel, Pratik; Migliore, Christina; Minerowicz, Christine; Madan, Nikhil
Abstract : Follicular bronchiolitis (FB) is a rare bronchiolar disorder associated with hyperplasia of the bronchial-associated lymphoid tissue (BALT). It is characterized by the development of lymphoid follicles with germinal centers in the walls of small airways. It falls under the category of lymphoproliferative pulmonary diseases (LPDs) and commonly occurs in relation to connective tissue disease, immunodeficiency, infections, interstitial lung disease (ILD), and inflammatory airway diseases. Computerized tomography (CT) findings include centrilobular nodules with patchy ground glass infiltrate, tree-in-bud findings, and air trapping. It can very rarely present as diffuse cystic lung disease. We present two cases of FB. The first case is associated with Human Immunodeficiency Virus (HIV) infection and asthma with diffuse cystic changes on the CT. The second case is associated with reactive airway disease and gastroesophageal reflux disease (GERD) with the classic centrilobular nodules and ground glass opacities on the CT.